Analisis Faktor-Faktor Yang Mempengaruhi Risiko Sistematis (Beta) Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2009-2014 - Aji, Rio Satriyo; Prasetiono, Prasetiono (Diponegoro Journal of Management, 2015)
This study aims to determine the effect of Asset Growth, Firm Size, Current Ratio, Financial Leverage, and Operating Leverage on stock beta. This study used five independent variables, namely Asset Growth, Firm Size, Current Ratio, Financial Leverage, and Operating Leverage, with one dependent variable is stock beta.Sampling technique used was purposive sampling criteria (1) company have already listing before the end observation period. (2) company listed in Indonesia Stock Exchange and has the most complete financial statements and have been published during the observation period from 2009 to 2014. (3) company has the most complete of financial variabels (Asset Growth, Firm Size, Current Ratio, Financial Leverage, and Operating Leverage) which will be used to research samples in the period of 2009-2014. Data obtained by the publication of financial statements listed on the website of Indonesia Stock Exchange. The obtained sample number is 22 companies. Analysis technique used is multiple regression. Before that, the assumptions of classical test and test hypotheses using t-statistics, testing the coefficient of determination and F-statistics to test the effect of the joint-the same as the level of significance of 5%. It also tested the classical assumptions that included tests of normality, multicollinearity test, test of heteroscedasticity, and autocorrelation test.Based on the results of data analysis, this research finds that Firm Size, Financial Leverage, dan Operating Leverage have positive but not significant impact on stock beta. The variable Current Ratio has a negative effect but not significant. The variable Asset Growth has a negative effect and significant on stock beta